Aggravating Language Used by Male and Female Characters’ in The Bad Boys Movies - Pamuji, Indah Ratri Sekar; Pradipta, Bramantya (State University of Makassar, 2025)
This research aims to analyze the types of aggravating language, and find differences in the use of aggravating language in characters’ utterances in Bad Boys for Life (2020) and Bad Boys Ride or Die (2024). This research uses a descriptive qualitative method. This study uses data sources from the utterances of the movies Bad Boys for Life (2020) and Bad Boys Ride or Die (2024) and uses data on all characters in the movies Bad Boys for Life (2020) and Bad Boys Ride or Die (2024). The research used theory by Lachenicht (1980) to analyze aggravating language. The results of this study are 50 aggravating language, 6 off-record, 10 bald on record, 18 positive aggravation, and 16 negative aggravation. The study indicated that male characters often using aggravating language than female characters to assert dominance of their position and show power to the interlocutor, as well as illustrating how the roles of men and women in socializing, especially the intent and purpose in using aggravating language. Keywords: Aggravation Strategy; Language; Movies Bad Boys; Pragmatics; Speech Act